The role of the social environment in actualizing personal social responsibility - Kostiuk, Sofiia (Psychological Prospects Journal, 2023)
Purpose. The Ukrainian society's current tasks are to activate members' involvement in improving society's well-being in the near and distant time perspective, formatting equal opportunities for personal development, and the constructive protection of individual interests, considering the interests of society. Effective changes involve the development of the social responsibility of a person as a subject of social interaction. Personal social responsibility is the willingness to voluntarily, based on understanding and accepting the social significance of their actions, undertake a duty to act for the benefit of society: participate in solving social problems and preventing their occurrence in the near and distant time horizon while maintaining personal welfare. Being a member of a society, a person is simultaneously a subject (as a driver of social change) and an object of the social environment (as a representative of social groups, institutions, and organizations with established norms and generally accepted rules of activity). The purpose of the article is to reveal the social environment's role in actualizing personal social responsibility.Methods. A systematic review of empirical studies of the personal social responsibility factors.Results. The social environment (family, close circle/friends, educational environment, working environment, state/self-governing bodies) affects the actualization of personal social responsibility. In particular, socially responsible values ​​and norms (formal and informal), as characteristics of the social environment, are a factor in the formation and moderator of the manifestation of a person's social responsibility; respect, trust, and support as characteristics of interpersonal relations in a social environment are positively related to personal social responsibility.Conclusions. The potentially positive influence of the social environment on personal social responsibility can be realized through the development of corporate social responsibility of institutions and organizations at the legislative level.
Keywords: social responsibility; responsible behaviour; corporate social responsibility; social wellbeing